Relationship between Learning Supervision and Work Motivation with the Performance of Madrasah Teacher Ibtidaiyah Sub-district of Padang Tualang - Mahlil; Muhammad Rivai (Britain International for Academic Research (BIAR) Publisher, 2019)
One of the efforts given to assist teachers in improving their performance is learning supervision services and work motivation. In this case the role of the madrasa head is to carry out supervision of learning. Supervision of madrasa head learning is very meaningful because madrasa head is a person who immediately understands and sees the reality of the abilities possessed by the teacher. This study deals with relationship between learning supervision and work motivation with the performance of Madrasah teacher Ibtidaiyah Sub-district of Padang Tualang. This research is a quantitative study using the correlation research method. The results shows that providing supervision of madrasah head learning and work motivation together can improve teacher performance with a linearity line Ŷ = 95.92 + 0.363X1 + 0.515X2.